PENGEMBANGAN BAHAN AJAR BERBASIS FLIPPED LEARNING PADA MATERI DIFERENSIAL UNTUK PESERTA DIDIK KELAS XI SMA/MA - Ravi Kurnia (Jurnal Edukasi dan Penelitian Matematika, 2022)
Technology based teaching materials are supporting the learning process in the current digital era, because they help students build their mathematical understanding actively and independently. This study aims to develop teaching materials based on Flipped Learning on differential materials for class XI SMA/MA that are valid and practical. This type of research is development, with the Plomp model consisting of the initial research phase and the development or prototyping phase. The initial research stage includes needs analysis, student analysis, curriculum analysis and concept analysis. The development or prototyping phase is the stage for designing teaching materials. In Prototype 1, a self-evaluation was carried out. In Protoype 2, expert reviews were conducted to test the validity of teaching materials. In Prototype 3, a one-to-one evaluation was conducted by testing teaching materials to three students with different abilities. In Prototype 4, a small group evaluation was conducted for nine students. Small group evaluation is carried out to determine the practicality of teaching materials. The results showed that Flipped Learning-based teaching materials for differential materials had a level of validity in the very valid category, the level of practicality in the practical category. Based on these results, it can be concluded that the teaching materials produced are valid and practical. Keywords __ Teaching materials, Flipped Learning, Plomp, Differential